4-1BB/4-1BBL Interaction Promotes Obesity-Induced Adipose Inflammation by Triggering Bidirectional Inflammatory Signaling in Adipocytes/Macrophages. (17th December 2012) - Tu, Thai Hien; Kim, Chu-Sook; Goto, Tsuyoshi; Kawada, Teruo; Kim, Byung-Sam; Yu, Rina
Abstract : Obesity-induced adipose inflammation is characterized by recruitment of macrophages to adipose tissue and release of inflammatory cytokines. 4-1BB, a costimulatory receptor, modulates inflammatory processes through interaction with its ligand 4-1BBL on immune cell surfaces. In this study, we examined whether a 4-1BB/4-1BBL interaction between adipocytes and macrophages participates in obesity-induced adipose inflammation. We found that 4-1BB was expressed on adipocytes and was upregulated by obesity-related factors, which also enhanced 4-1BBL expression on macrophages. 4-1BB and/or 4-1BBL agonists, respectively, activated inflammatory signaling molecules (MAPK/I κ B α and MAPK/Akt) in adipocytes and macrophages and enhanced the release of inflammatory cytokines (MCP-1, TNF- α, and IL-6). Moreover, disruption of the 4-1BB/4-1BBL interaction decreased the release of inflammatory cytokines from contact cocultured adipocytes/macrophages. These findings indicate that 4-1BB/4-1BBL-mediated bidirectional signaling in adipocytes/macrophages promotes adipose inflammation. 4-1BB and 4-1BBL may be useful targets for protection against obesity-induced adipose inflammation.